Livestock intensification and the role of finance in the Food System Transformation in Brazil - Koberle,A; Holtedahl,P (Food Systems Economics Commission, 2024)
The potential for the Brazilian cattle sector to increase production while concurrently reducingpressure for land expansion is widely recognized. With mounting evidence that land use changeamplifies the impacts from global climate change, a transition to climate resilient and low-carbonagriculture becomes imperative and unavoidable. This analysis explores possible contributions ofthe Brazilian beef cattle sector can make to a Food System Transition (FST). The results of thisanalysis show a large potential to increase productivity and spare land for other uses, but severalsocioeconomic and political economy challenges will need to be overcome, such as increasingaccess to finance and technical assistance as well as a tightening of environmental governanceacross the country. Adopting intensification practices can increase farm profitability and havepayback periods of months to a couple of years but require up-front investments that posechallenges for farmers with low access to finance. While results indicate that realizing the landsparing potential of the cattle sector is not free from macroeconomic frictions, there are alsosocioeconomic opportunities for the country in a global FST trajectory. However, capturing theopportunities will require well-designed policies that can link multiple objectives and maximize thesynergies across the environmental, health, and inclusion domains.